Strategic and natural risk in entrepreneurship: an experimental study - Morgan, John; Orzen, Henrik; Sefton, Martin; Sisak, Dana (Wiley, 2016)
We report on the results of experiments where participants choose between entrepreneurship and an outside option. Entrepreneurs enter a market and then make investment decisions to capture value. Payoffs depend on both strategic risk (i.e. the investments of other entrepreneurs) and natural risk (i.e. luck). Absent natural risk, participants endogenously sort themselves into entrepreneurial and safe types, and returns from the two paths converge. Adding natural risk fundamentally changes these conclusions: Here we observe excessive entry and excessive investment so that entrepreneurs earn systematically less than the outside option. These payoff differences persist even after many repetitions of the task. With a risky outside option, entry further increases and about one-third of entrepreneurs adopt a passive strategy, investing little or nothing. Finally, we examine an environment where an individual must become an entrepreneur but chooses the stakes over which she will compete. Due to under-entry and under-investment in the high stakes setting, the returns gap grows to over 15 percentage points. A two-factor model incorporating loss aversion and love of winning can rationalize these returns patterns.